Comparative effect of local and foreign commercial feeds on the growth and survival of Clarias gariepinus juveniles - Moshood Keke Mustapha; Bolarinwa Faith Akinware; Charles A. Faseyi; Aminat Ajoke Alade (Journal of Fisheries, 2014)
Growth and survival of Clarias gariepinus juveniles fed with a local feed and coppens commercial feed were observed for 16 weeks at  the laboratory of the Department of Zoology, University of Ilorin, Nigeria. The proximate compositions and economics of the feeds and water quality of the cultured tanks were assessed. Fish fed with coppens showed significant (P<0.05) higher weight increase, specific growth rate, protein efficiency ratio and low food conversion ratio than fish fed with local feed. Significant (P<0.05) higher mortality were recorded in fish fed with the local feed. The growth performance was a reflection of the proximate composition of the feeds with local feed having low crude protein (10.95%), lipid (3.95%) and ash (4.92%) when compared to coppens which had 42% crude protein, 12% lipid and 9.5% ash with protein being most significant. Carbohydrate (69.90%) and crude fiber (2.88%) were higher in the local feed than in coppens with an imbalance in carbohydrate and lipid ratio. Mortality was attributed to stress resulting from the poor quality of the feed. Cost of feeding with local feed to a weight gain of 31.67g was ₦80, while the cost of feeding with coppens to a weight gain of 148.58g was ₦16.